3(x+2)-12=5x+6-4x

Simple and best practice solution for 3(x+2)-12=5x+6-4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+2)-12=5x+6-4x equation:


Simplifying
3(x + 2) + -12 = 5x + 6 + -4x

Reorder the terms:
3(2 + x) + -12 = 5x + 6 + -4x
(2 * 3 + x * 3) + -12 = 5x + 6 + -4x
(6 + 3x) + -12 = 5x + 6 + -4x

Reorder the terms:
6 + -12 + 3x = 5x + 6 + -4x

Combine like terms: 6 + -12 = -6
-6 + 3x = 5x + 6 + -4x

Reorder the terms:
-6 + 3x = 6 + 5x + -4x

Combine like terms: 5x + -4x = 1x
-6 + 3x = 6 + 1x

Solving
-6 + 3x = 6 + 1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-6 + 3x + -1x = 6 + 1x + -1x

Combine like terms: 3x + -1x = 2x
-6 + 2x = 6 + 1x + -1x

Combine like terms: 1x + -1x = 0
-6 + 2x = 6 + 0
-6 + 2x = 6

Add '6' to each side of the equation.
-6 + 6 + 2x = 6 + 6

Combine like terms: -6 + 6 = 0
0 + 2x = 6 + 6
2x = 6 + 6

Combine like terms: 6 + 6 = 12
2x = 12

Divide each side by '2'.
x = 6

Simplifying
x = 6

See similar equations:

| 58=4h | | 9.05x=27.15 | | 6/2x3 | | 0.5(r-12)=4 | | (x)/(4)-1=7 | | 0.4(b+2)=2 | | 9(x-2)+1=9x-16 | | 19-6(-k+4)= | | .50(x-3)=2(x-3) | | 6n+3n=108 | | f(-4)+f(3)= | | 30u^5v^3x^6+24u^8v^9= | | (4-2i)(3+i)= | | r*2+2r+12=0 | | 5.6+x=8.4 | | 3(19/-23)=20(-19/-23)-7 | | 3(19/-23)=20(-19/23)-7 | | 16x-3x=3(2-x) | | (3x^7)(-5x^3)= | | 12=-7y | | Xa+xb=3c | | x^4-x^3-24x^2+37x+60=0 | | 7(-8c+9a)= | | -3(4m+7)= | | 12=-11y+4y | | (-7v-6)-(2v-4)= | | 6(2+15x)= | | 2/7-1/14 | | 32b-4+-2b-1= | | 10+5r=10-r | | (2/x)-x=(-23/5) | | (7/8)/m=(1/7) |

Equations solver categories